Integrating TPACK into a Problem-Based Learning Model to Improve Mathematics Achievement among Junior High School Students - Manurung, Siti Aminah; Lase, Umbuzaro (Al'Adzkiya Journal, 2025)
This study was initiated due to the low mathematics achievement of seventh-grade students at SMP Negeri 3 Satu Atap Idanotae, South Nias Regency, particularly on the topic of integers. Student performance was below the Minimum Mastery Criteria (KKM) set at 67, with only 9 out of 21 students (approximately 44%) meeting the required standard. The primary aim of this research was to improve student learning outcomes through the implementation of a Problem-Based Learning (PBL) model integrated with the TPACK approach. The study employed a Classroom Action Research (CAR) design and was conducted in two cycles during the 2018/2019 academic year. The findings indicate that the application of the PBL model effectively enhanced student learning outcomes in the topic of integers. Increased teacher engagement in the learning process was also observed, attributed to the use of the PBL model. Student achievement showed a consistent upward trend across the cycles. Prior to the intervention, only 9 students met the KKM with a class average of 44%. In the first cycle, 15 students achieved the KKM, raising the class average to 67%, and in the second cycle, 19 students met the KKM with a class average of 93%. These results demonstrate the positive impact of the PBL model in improving students’ mathematical understanding and overall academic performance.